The composition of foetal and maternal blood during parturition in the ewe - Comline, R. S. (1972)
1. Changes in the composition of foetal and maternal blood have been followed during the last 5-10 days of gestation and throughout parturition in the conscious sheep. 2. Catheters were placed in the foetal inferior vena cava through a tarsal vein and in a maternal uterine vein in ten ewes under sodium pentobarbitone anaesthesia. In four of the foetuses blood pressure and heart rates were recorded before and during parturition from an arterial catheter. 3. Foetal blood gas tensions, pH and PCV remained stable during the latter part of gestation and throughout labour until 15 min before delivery, when P(O)(2) and pH fell while PCV and P(CO)(2) rose in about 50% of the foetuses examined. 4. Metabolite levels were also relatively stable at the end of gestation. Plasma glucose in both maternal and foetal blood rose during the hour before birth, while foetal plasma lactate was elevated as early as 4 hr before birth and was unrelated to any maternal changes. Foetal fructose levels were maintained until after delivery. 5. Rises in foetal blood pressure before birth were associated with uterine contractions. Foetal heart rate changes during labour varied in different individuals. The heart rate either fell gradually before birth or there was little change until a sudden drop at delivery. 6. The most striking changes in the lamb occurred at, or a few minutes after, birth; pH and P(O)(2) fell, P(CO)(2) and PCV rose, and bradycardia at delivery was succeeded by prolonged tachycardia. There were marked increases in plasma glucose and lactic acid at this time. 7. P(O)(2) rose rapidly once respiration was established, while pH and P(CO)(2) levels were restored within ½-1 hr. Plasma FFA levels rose rapidly in the lambs 10-30 min after birth and remained high, while plasma glucose, lactate and fructose concentrations declined slowly in the 1-2 hr after birth, although suckling raised the plasma glucose levels. Considerable individual variation in the metabolite levels was found in both ewes and lambs. 8. In the majority of ewes delivery was associated with an abrupt maternal hyperglycaemia, with a much smaller rise in lactate and virtually no change in maternal blood gases or pH. 9. These findings are discussed in relation to existing information on new-born lambs and the human infant during birth.